2016
DOI: 10.17795/bhs-36162
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Combined Aerobic and Resistance Training on Hepatic Enzymes in Males With Nonalcoholic Fatty Liver

Abstract: Background: Nonalcoholic fatty liver disease (NAFLD) is a common liver disease associated with inactivity and obesity. Physical activity and exercise could affect the risk of NAFLD progression by improving the hepatic lipid profiles. Objectives: The current study aimed to evaluate the efficacy of combination of aerobic and resistance training on hepatic enzymes in males with NAFLD. Patients and Methods: The study was a randomized controlled trial. Thirty-two untrained males with NAFLD (aged = 32.93 ± 2.15 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…Such exercises were shown to decrease blood pressure and IHL and improve insulin resistance [ 19 , 21 ]. Moreover, a combination of aerobic exercise and resistance training was also shown to improve the metabolic parameters known to interfere in NAFLD development and offer a protective role against it [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such exercises were shown to decrease blood pressure and IHL and improve insulin resistance [ 19 , 21 ]. Moreover, a combination of aerobic exercise and resistance training was also shown to improve the metabolic parameters known to interfere in NAFLD development and offer a protective role against it [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In different research, it was reported that exercise affects muscle damage markers [15]. It was concluded that combined aerobic and resistance exercises performed three days a week for 8 weeks had positive effects on liver enzymes in individuals with Nonalcoholic fatty liver disease [16]. Shamsoddini et al [17] have emphasized that aerobic exercise and resistance training lead to decreases in AST and ALT values.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the effects of exercise on the hepatic enzymes are completely contradictory in related studies, 1,17,18,26 it seems that the exact mechanisms are needed to be further evaluated regarding that whether the elevation in serum ALP is an exercise induced-positive physiological or a pathological adaptation. On the other hand, due to the sedentary lifestyle and physically inactive status in overweight PMWs, it is likely that any intensity of aerobic exercise may cause additional pressure on body organs such as the liver and CVS.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 However, many studies have reported effects of aerobic training on the hepatic and lipid profiles, but their results are contradictory. 1,[17][18][19] On the other hand, in aged individuals and especially in postmenopausal women (PMWs), the accumulation of visceral fat due to a reduction in sex hormones such as estrogen and progesterone leads to an increase in CVS, metabolic and liver diseases. 13 In other words, in the menopause period, the relationships between estrogen reduction and biochemical effects due to aging process results in the hepatic damage.…”
Section: Assessment Of Hepatic and Lipid Profiles Following 12 Weeks mentioning
confidence: 99%
See 1 more Smart Citation